The sloan digital sky survey peculiar velocity catalogue. Issue 1 (20th June 2022) - Howlett, Cullan; Said, Khaled; Lucey, John R; Colless, Matthew; Qin, Fei; Lai, Yan; Tully, R Brent; Davis, Tamara M
ABSTRACT: We present a new catalogue of distances and peculiar velocities (PVs) of 34 059 early-type galaxies derived from fundamental plane (FP) measurements using data from the Sloan Digital Sky Survey (SDSS). This 7016 deg^2 homogeneous sample comprises the largest set of PVs produced to date and extends the reach of PV surveys up to a redshift limit of z = 0.1. Our SDSS-based FP distance measurements have a mean uncertainty of 23 per cent. Alongside the data, we produce an ensemble of 2048 mock galaxy catalogues that reproduce the data selection function, and are used to validate our fitting pipelines and check for systematic errors. We uncover a significant trend between group richness and mean surface brightness within the sample, which may hint at an environmental dependence within the FP or the presence of unresolved systematics, and can result in biased PVs. This is removed by using multiple FP fits as function of group richness, a procedure made tractable through a new analytic derivation for the integral of a three-dimensional (3D) Gaussian over non-trivial limits. Our catalogue is calibrated to the zero-point of the CosmicFlows-III sample with an uncertainty of 0.004 dex (not including cosmic variance or the error within CosmicFlows-III itself), which is validated using independent cross-checks with the predicted zero-point from the 2M++ reconstruction of our local velocity field. Finally, as an example of what is possible with our new catalogue, we obtain preliminary bulk flow measurements up to a depth of 135 h^-1Mpc . We find a slightly larger-than-expected bulk flow at high redshift, although this could be caused by the presence of the Shapley supercluster, which lies outside the SDSS PV footprint.